Pengaruh Pengetahuan Terhadap Perilaku Penerimaan Terapi Pencegahan Tuberculosis (TPT) Pada Kontak Serumah - Santoso, Mohamad Arif Budi; Dhonna Anggreni (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Predisposing factors are one of the factors that influence a person's behavior. One of the dominant predisposing factors is knowledge. The purpose of this study was to analyze the influence of knowledge on the behavior of TPT acceptance in household contacts of tuberculosis patients in the working area of the Mojokerto District Health Office. This study used a crossectional design with a population of household contacts of tuberculosis patients in the working area of the Mojokerto District Health Office. Samples were taken randomly from subjects who met the inclusion criteria, totaling 90 people. Data were collected using a questionnaire and then analyzed using the fisher exact test. The results showed that most respondents had Tuberculosis Preventive Therapy (TPT) acceptance behavior in the good category, namely 72 people (80%) and had knowledge in the good category (71.10%). The results of data analysis showed that there was an influence of knowledge on the behavior of TPT acceptance behavior in household contacts of tuberculosis patients (pvalue=0.000). Knowledge influences an individual's understanding which affects the emergence of motivation to act. The higher the knowledge, the better the behavior of accepting TPT in household contacts of tuberculosis patients. Therefore, efforts to increase knowledge are very important for patients to improve the acceptance of TPT in household contacts of tuberculosis patients